2012
DOI: 10.1503/cmaj.111123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of assessing the productivity of faculty in academic medical centres: a systematic review

Abstract: Strategies introduced to assess productivity as part of a compensation scheme appeared to improve productivity in research activities and possibly improved clinical productivity, but they had no effect in the area of teaching. Compensation increased at both group and individual levels, particularly among junior faculty. Higher quality evidence about the benefits and harms of such assessment strategies is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 19 publications
3
58
0
3
Order By: Relevance
“…For example the ACS surgeon is additionally responsible for complex counseling, end of life care, ICU coverage, consult responsibility, and trauma amongst other aspects of care. Arguments against RVUs for productivity measurement come from academic physicians and surgeons, whose time is spent in the education of trainees, research pursuits, or innovation, none of which can be captured or acknowledged in a system that only recognizes RVU-defined productivity 15,16 . This RVU dichotomy simply does not reflect ACS work.…”
Section: Discussionmentioning
confidence: 99%
“…For example the ACS surgeon is additionally responsible for complex counseling, end of life care, ICU coverage, consult responsibility, and trauma amongst other aspects of care. Arguments against RVUs for productivity measurement come from academic physicians and surgeons, whose time is spent in the education of trainees, research pursuits, or innovation, none of which can be captured or acknowledged in a system that only recognizes RVU-defined productivity 15,16 . This RVU dichotomy simply does not reflect ACS work.…”
Section: Discussionmentioning
confidence: 99%
“…The authors noted, however, that "two of these programs provided a credit for time spent teaching and the third set an expectation for faculty participation in educational activities," thus explicitly attempting to mitigate the impact of the productivity demands (p. 257). Another group reviewed eight studies that linked compensation to productivity measures (clinical, research, and teaching) and found that the plans "appeared to improve productivity in research activities, possibly improved clinical productivity but had no effect in the area of teaching" [16] (p. 5). By contrast, a more recent study in a large urban academic internal medicine department that had recently implemented clinical productivity work targets found that 86% of faculty reported being less likely to engage in activities that did not directly count toward productivity targets, and 75% specifically reported a decrease in time spent teaching.…”
Section: Historical Factorsmentioning
confidence: 99%
“…Participant No. 1 said: "The response to the Non-Educational requirements is what exists at the moment and it is somehow forced into medical 4 Iran Red Crescent Med J. 2017; 19 (7):e57566.…”
Section: Establishing a New Residency Programmentioning
confidence: 99%
“…Providing adequate faculty members has been very obvious in medical schools. Medical members are increasingly considered as the most important capital of medicine schools (2) because of their specific responsibilities beside common roles that all faculties have (3,4). Thus, every faculty of medicine needs sufficient numbers of qualified members in order to accomplish the assigned tasks (5).…”
Section: Introductionmentioning
confidence: 99%